IJCM_142A: Perceptions and practices regarding the use of helmets among college students of Mangalore city- A cross sectional study - Jain Animesh; Aishwarya Guntur; Singh Monika; Kamat Rohaan; Guliani Astha; Sattigeri Amitavikram (Wolters Kluwer Medknow Publications, 2024)
Background: Road traffic injuries remain a significant public health concern, contributing to a rising number of fatalities and hospitalizations, in India. Despite the proven effectiveness of helmets, cultural and practical barriers persist, especially among the youth in India. Objectives: To assess the perceptions and practices regarding the use of helmets among different college students of Mangalore city. Methodology: This cross-sectional study was conducted in Mangalore, Karnataka, focusing college students from selected institutions. Convenience sampling was employed, with a calculated sample size of 270, and data was collected from 273 participants. Statistical analyses, including chi-square tests and percentages, were performed using SPSS version 11.5. Results: Of the 272 respondents (97.84% response rate), 85.66% were two- wheeler users, with 56.6% regularly using helmets. Full-face helmets were the most common choice, and 43.9% began using helmets following the implementation of helmet laws. Main reasons for non-compliance included concerns about excessive heat, impact on appearance, and handling difficulties. Awareness of penalties for law violation varied, with 53% aware for riders and 33% for pillion riders. While 41.5% deemed the penalty appropriate, 65% believed no one should be exempt from the law. Surprisingly, 45.16% advocated for the abolishment of the law. Conclusion: The study found that helmet usage is primarily driven by safety concerns, but a significant portion only started using them after legislation enforcement. Barriers to compliance included heat discomfort and aesthetic concerns. Despite awareness, a significant proportion expressed a desire for helmet laws' abolishment, highlighting a complex relationship between awareness and compliance.